Dual Band Axially Displaced Ellipse Reflector Antenna for Radar and Broadband Applications - Ulusoy, Emre; Turk, Ahmet Serdar (IEEE, 2017)
In the scope of this paper a dual-reflector antenna called Axially Displaced Ellipse (ADE) antenna for being used in X-Band, K-Band radar and any other broadband applications were focused. The antenna design consists of feed antenna and dual-reflector configuration. Broadband Double Ridged Horn (DRH) antenna is designed and used as a feeder. Most used radar frequencies at X-Band and K-Band which are 10 GHz, 24 GHz, 35 GHz are considered for design and performance. The simulation program CST Microwave Studio was used to test the antenna designs by simulating them. The goal of this study is designing the antenna with a good value of S-11 and remarkable radiation characteristics along the whole frequency range.
Keywords: Engineering; Remote Sensing; Telecommunications